Perceptions and insights on industrial training: a study of IIUM mechatronics engineering students - Wahid, Azni Nabela; Azmi, Nur Liyana; Mokhtar, Suhaily (PENERBIT UniMAP, 2026)
Industrial training plays a pivotal role in providing students with experiential learning opportunities that enhance their technical competence and professional readiness. This study presents an analysis of Mechatronics Engineering students’ perceptions of the industrial training programme at the International Islamic University Malaysia (IIUM). A total of 56 students participated in a survey evaluating the quality of training in the host company, ability to apply knowledge, career awareness, and faculty coordination. Quantitative data was complemented by qualitative insights derived from open-ended student reflections. Survey results reveal high satisfaction with supervision quality, mentorship, and work environment. Findings indicate that most students acknowledged that the internship is instrumental in bridging theoretical knowledge with real-world applications and in clarifying their career aspirations. Suggestions for improvement include extending the internship period and enhancing placement support through stronger university–industry partnerships. Overall, the findings revealed the effectiveness of the industrial training programme in fostering professional competencies while highlighting areas for improvement for enhanced experiential learning.